Socialization of work base learning-based industrial practice platforms for students, vocational teachers, and industrial partners - Dwi Jatmoko; Suyitno Suyitno; Aci Primartadi; Murhadi Murhadi (Universitas Muhammadiyah Magelang, 2022)
This community service has a goal, including providing information for students, industry, and academics about the use of work-based learning-based industrial practice platforms. This service uses a structured method, starting with a theory about computer technology, followed by direct practice by the presenters with the concept of direct practice to teach community service participants. The socialization material starts with the explanation of the platform flow and the functions of each feature. The results of this socialization received quite a positive response, Utilization of computer technology with the creation of a work base learning-based industrial practice platform is very helpful in providing administrative management for the independent learning internship program at the independent campus. This community service in the form of socialization received good and positive responses, especially in the design of a work-based learning-based industrial practice platform, which got a score of 3.9, which means that they are very satisfied with the work-based learning platform.